The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1017/jfm.2021.42
|View full text |Cite
|
Sign up to set email alerts
|

Scalings of the mixing velocity for buoyancy-driven instabilities in porous media

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Vice versa , a diffusive-layer convection instability (DLC) can develop if A diffuses faster than B . While under nonreactive conditions all of these scenarios develop symmetrically across the initial contact line between the two layers, a chemical reaction as simple as an A + B → C process can profoundly modify the symmetry of the fingered interface depending on the local density change induced by the reaction. …”
Section: Introductionmentioning
confidence: 99%
“…Vice versa , a diffusive-layer convection instability (DLC) can develop if A diffuses faster than B . While under nonreactive conditions all of these scenarios develop symmetrically across the initial contact line between the two layers, a chemical reaction as simple as an A + B → C process can profoundly modify the symmetry of the fingered interface depending on the local density change induced by the reaction. …”
Section: Introductionmentioning
confidence: 99%
“…With respect to the properties of the species involved, possible flow configurations can be grouped in three main categories: presence of one chemical, presence of two chemicals with different diffusion coefficients, and presence two species that can chemically react [20]. With the aid of numerical simulations and experiments, Lemaigre et al [21] observed that in absence of chemical reactions the mixing region grows symmetrically with respect to the initial position of the interface: The growth occurs at a velocity that depends on the nature of the fluids involved, i.e., it is controlled by the diffusivity of the species and by the initial density difference [22]. The evolution of the system is different in presence of chemical reactions and moderate density contrast.…”
Section: Introductionmentioning
confidence: 99%
“…However, we neglect the effects of gravity, which would come into play at later times. This leaves aside buoyancy-driven flows in miscible and immiscible fluids [14]. Such cases correspond, for instance, to the early stages of the injection of hot water into heavy and extraheavy oil reservoirs (immiscible fluids) and to the injection of hot or cold water into geothermal aquifers (miscible fluids).…”
Section: Introductionmentioning
confidence: 99%